Meningkatkan Efektivitas Penulisan Ilmiah dengan Pendampingan Aplikasi Artificial Intelligence (AI) untuk Guru di Baso Kabupaten Agam Sumatera Barat - Efriyanti, Liza (STIE Pelita Nusantara, 2024)
This training aims to enhance the effectiveness of scientific writing for teachers in Baso, Agam Regency, West Sumatra, with the aid of Artificial Intelligence (AI) applications. In the context of expanding education, it is crucial for teachers to produce quality and relevant scientific writing. However, the scientific writing process often presents various challenges. Therefore, this training aims to enhance understanding of basic AI concepts and teach the effective use of relevant AI applications in scientific writing. The training includes presentations, discussions, practical demonstrations, and self-directed exercises to provide trainees with the necessary knowledge and skills. The training evaluation results indicate that participants improved their understanding of AI concepts, mastered the use of AI applications, and reported significant improvements in the efficiency and quality of their scientific writing. Additionally, the training successfully enhanced participants' digital literacy and made a positive contribution to education in the Baso region. It is expected that the training results will be practically applied in teachers' learning and research activities, and will have a sustainable impact on the development of education in the area. Keywords: Artificial Intelligence (AI), effectiveness, training, scientific writing, teachers